Dendrobium spectabile (Blume) Miq. IN VITRO CULTURE AND ITS ACCLIMATIZATION ON MUS MEDIA WITH ANTIMICROBIAL AND ALCOHOLIC SUGAR SUPPLEMENTATION - Untung Santoso; Y.Sri Wulan Manohara; Kusriningrum Rochiman S. (The East Java Biological Society, 2014)
Germination and development of orchid seed of Dendrobium spectabile through in vitro method has been done with good result and yielded many seeds. Different acclimatization approach was developed with sphagnum moss medium which supplemented with the same nutrition as MUS medium. Alcoholic sugar was supplemented to increase medium moisture and antimicrobial was added to minimalized contamination which can harm orchid seeds. Planlet adaptation ability to drought stress which resulted from in vitro culture can be improved using the new medium. The medium will increase the probability of seed survival also it will normalize seed development through the acclimatization process.